FAKTOR INTERNAL DAN EKSTERNAL YANG MEMPENGARUHI KEPUTUSAN CALON MAHASISWA BARU DALAM MEMILIH PERGURUAN TINGGI SWASTA DI KOTA SURABAYA - Asmirin Noor; Pierre Patarianto (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2015)
Most of private universities in the city of Surabaya, which increasingly lead to competition among private universities become more stringent. Currently private college education is required to be able to optimize the number of new students each year to exist. Many factors affect prospective students in choosing a college. Internal factors, namely Product (Image Campus, System and Concept Learning, Accreditation Status and Lecturer professional), Price (Low Cost, Payment Terms, Pieces Bea Education and Scholarship), place (library, Conditions Building, Completed facility, Environmental conditions Campus and Campus Services) and Promotion (Successful Alumni and guarantee getting a job) and external factors such as the Effects of Family, Social Class, Culture and the Reference Group. Internal independent variable factor that consists of product and promotion significantly influence the decision to buy at STIE Mahardhika Surabaya. External independent variable factor that consists of family influence, culture and reference group significantly influence the decision to buy at STIE Mahardhika Surabaya. The independent variable variable product is the dominant influence on the decision to buy at STIE Mahardhika Surabaya